Plant nuclear shape is independently determined by the SUN-WIP-WIT2-myosin XI-i complex and CRWN1 - Zhou, Xiao (Nucleus, 2015)
Nuclei undergo dynamic shape changes during plant development, but the mechanism is unclear. In Arabidopsis, Sad1/UNC-84 (SUN) proteins, WPP domain-interacting proteins (WIPs), WPP domain-interacting tail-anchored proteins (WITs), myosin XI-i, and CROWDED NUCLEI 1 (CRWN1) have been shown to be essential for nuclear elongation in various epidermal cell types. It has been proposed that WITs serve as adaptors linking myosin XI-i to the SUN-WIP complex at the nuclear envelope (NE). Recently, an interaction between Arabidopsis SUN1 and SUN2 proteins and CRWN1, a plant analog of lamins, has been reported. Therefore, the CRWN1-SUN-WIP-WIT-myosin XI-i interaction may form a linker of the nucleoskeleton to the cytoskeleton complex. In this study, we investigate this proposed mechanism in detail for nuclei of Arabidopsis root hairs and trichomes. We show that WIT2, but not WIT1, plays an essential role in nuclear shape determination by recruiting myosin XI-i to the SUN-WIP NE bridges. Compared with SUN2, SUN1 plays a predominant role in nuclear shape. The NE localization of SUN1, SUN2, WIP1, and a truncated WIT2 does not depend on CRWN1. While crwn1 mutant nuclei are smooth, the nuclei of sun or wit mutants are invaginated, similar to the reported myosin XI-i mutant phenotype. Together, this indicates that the roles of the respective WIT and SUN paralogs have diverged in trichomes and root hairs, and that the SUN-WIP-WIT2-myosin XI-i complex and CRWN1 independently determine elongated nuclear shape. This supports a model of nuclei being shaped both by cytoplasmic forces transferred to the NE and by nucleoplasmic filaments formed under the NE.